Pengaruh Variasi Panjang Serat Tebu Sebagai Bahan Tambah Terhadap Indeks Perendaman Campuran AC-BC - Armin Pareang; Alpius; Benyamin Tanan (Paulus Civil Engineering Journal, 2023)
The purpose of this study was to determine the effect of varying the length of sugarcane fiber on the soaking index of the AC-BC mixture when used as an additive. Sugar cane fiber is an organic waste produced by sugar plantations. In the research, sugarcane fiber was used as an additive to the asphalt mixture as an asphalt binder. Through the Marshall immersion test, the AC-BC mixture was obtained with variations in the length of the sugarcane fiber 3 cm, 4 cm, 5 cm, 6 cm and 7 cm for the soaking duration of 0 .5 hours and 24 hours. This method uses several tests on the characteristics of the aggregate and filler materials, after which a design is carried out for the AC-BC mixture and the Marshall immersion test is carried out in order to obtain the immersion index (IP), residual strength index (IKS) and durability values. From the test results using the Marshall immersion test method within 0.5 hours and 24 hours, the AC-BC mixture was obtained with variations in the length of the sugar cane fiber of 3 cm, 4 cm, 5 cm, 6 cm and 7 cm. The Marshall test results for the AC-BC mixture obtained the Immersion Index (IP), Residual Strength Index (IKS), and Durability. From these tests, the average IP value for the 3 cm fiber length variation was 93.20%, for the 4 cane fiber length variation. cm, which is 93.35% for the 5 cm long variation of cane fiber, which is 95.15% for the 6 cm long variation of cane fiber, which is 95.81% and for the 7 cm long variation of cane fiber, which is 98.92%.